2021
DOI: 10.3390/app12010404
|View full text |Cite
|
Sign up to set email alerts
|

End-to-End Deep Learning CT Image Reconstruction for Metal Artifact Reduction

Abstract: Metal artifacts are common in CT-guided interventions due to the presence of metallic instruments. These artifacts often obscure clinically relevant structures, which can complicate the intervention. In this work, we present a deep learning CT reconstruction called iCTU-Net for the reduction of metal artifacts. The network emulates the filtering and back projection steps of the classical filtered back projection (FBP). A U-Net is used as post-processing to refine the back projected image. The reconstruction is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…LIMAR is equivalent to NMAR, just without the tissue-normalization step. 18 Primarily in recent deep learning-based MAR methods, LIMAR and NMAR are the only reference algorithms, which are used in almost every publication for both conventional CT [19][20][21][22][23][24][25][26] as well as cone-beam CT. [27][28][29] Sinogram inpainting describes the replacement of the metal projections, mostly by interpolating linearly in between the metal boundaries of the uncorrected sinogram to minimize the impact of the metal projections onto the reconstructed image. Because all metal projections are considered invalid information, the resulting LI image contains strong interpolation artifacts, which blur surrounding tissue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LIMAR is equivalent to NMAR, just without the tissue-normalization step. 18 Primarily in recent deep learning-based MAR methods, LIMAR and NMAR are the only reference algorithms, which are used in almost every publication for both conventional CT [19][20][21][22][23][24][25][26] as well as cone-beam CT. [27][28][29] Sinogram inpainting describes the replacement of the metal projections, mostly by interpolating linearly in between the metal boundaries of the uncorrected sinogram to minimize the impact of the metal projections onto the reconstructed image. Because all metal projections are considered invalid information, the resulting LI image contains strong interpolation artifacts, which blur surrounding tissue.…”
Section: Introductionmentioning
confidence: 99%
“…LIMAR is equivalent to NMAR, just without the tissue‐normalization step 18 . Primarily in recent deep learning‐based MAR methods, LIMAR and NMAR are the only reference algorithms, which are used in almost every publication for both conventional CT 19–26 as well as cone‐beam CT 27–29 …”
Section: Introductionmentioning
confidence: 99%
“…Most of them can be categorized in the following two major groups: Image-based approaches [18][19][20] aim to correct artifacts solely in image space. In contrast, sinogram-based approaches [21][22][23] try to correct the information within the metal trace of the sinogram instead of applying linear interpolation. Hybrid approaches combine image-and sinogram-based methods.…”
Section: Introductionmentioning
confidence: 99%
“…Those could be carried over to various steps within iMAR or iMARv2, such as the metal segmentation, which is still based on a thresholding-based imaging mask 41 . Related recent studies in this area have already shown promising performance when incorporating deep learning into MAR by learning an end-to-end pipeline in either image, 42 sinogram space, 43 or mixed space 44 …”
Section: Discussion and Outlookmentioning
confidence: 99%